2020
DOI: 10.3390/cancers12030687
|View full text |Cite
|
Sign up to set email alerts
|

ATM-Deficient Cancers Provide New Opportunities for Precision Oncology

Abstract: Poly-ADP ribose polymerase (PARP) inhibitors are currently used in the treatment of several cancers carrying mutations in the breast and ovarian cancer susceptibility genes BRCA1 and BRCA2, with many more potential applications under study and in clinical trials. Here, we discuss the potential for extending PARP inhibitor therapies to tumours with deficiencies in the DNA damage-activated protein kinase, Ataxia-Telangiectasia Mutated (ATM). We highlight our recent findings that PARP inhibition alone is cytostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 99 publications
1
96
0
Order By: Relevance
“…PC remains one of the most lethal solid malignancies. The identification of damaging mutations in DDR system genes, including ATM , in 17–25% of this type of cancer and the recent suggestion that PARP inhibitors could have therapeutic potential in cancers with loss or mutation of ATM are opening up the possibility of new therapies, such as platinum and more recently PARP inhibitors, also in ATM -mutated patients with PC [ 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…PC remains one of the most lethal solid malignancies. The identification of damaging mutations in DDR system genes, including ATM , in 17–25% of this type of cancer and the recent suggestion that PARP inhibitors could have therapeutic potential in cancers with loss or mutation of ATM are opening up the possibility of new therapies, such as platinum and more recently PARP inhibitors, also in ATM -mutated patients with PC [ 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from TCGA Pan Cancer Atlas studies, available on c-Bioportal (Cerami et al 2012;Gao et al 2013) (accessed March 15, 2020 reveal that ATM is mutated in approximately 6% of all cancers (677 of 10,967 samples), with 766 identified mutations (522 missense, 230 truncating, 8 in-frame and 6 other) that are scattered throughout the coding sequence, with very few occurring in multiple tumour samples. An exception is R337C/H that occurs in 22 out of 677 (3%) of the samples analysed (discussed in Jette et al 2020). Moreover, the functional consequences of the vast majority of ATM mutations are unknown, thus screening patients by DNA sequence alone may not be informative.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, immunohistochemistry of ATM protein expression in lung adenocarcinoma patient samples revealed that over 40% had low protein expression, despite only 10% showing gene mutation (Villaruz et al 2016). In addition, promoter methylation has been shown to lead to ATM gene silencing in some cancer cells (Hirakawa et al 2019;Kim et al 2002;Jette et al 2020). Therefore, it is possible that more patient samples may lack ATM expression or function than indicated by exome sequencing alone and that methods for assaying ATM protein expression and/or activity will be required for patient selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The repression of either ATM or BRCA1 expression makes the cells hypersensitive to the treatment with olaparib, an FDA approved PARP inhibitor. 48,57,58 Hence, the relationship between the effect of olaparib, BRCA1 expression and miR-BARTs activity should be evaluated in NPC. Unfortunately, the NPC cell lines available in our laboratory…”
Section: F I G U R Ementioning
confidence: 99%